Results of management turnover in two irrigation districts in Colombia - Vermillion, Douglas L.; Garcés-Restrepo, C. (International Irrigation Management Institute, 1996)
Evaluates the turnover of two formerly government-managed irrigation districts in Colombia to the water users' associations. Impacts are analyzed in terms of the cost of irrigation to farmers and the government, the quality of water distribution, the sustainability of irrigation, the productivity of agriculture, and farmer income.